Entraining IDyOT: Timing in the Information Dynamics of Thinking - Forth, Jamie; Agres, Kat; Purver, Matthew; Wiggins, Geraint A. (Frontiers in Psychology, 2016)
We present a novel hypothetical account of entrainment in music and language, in context of the Information Dynamics of Thinking model, IDyOT. The extended model affords an alternative view of entrainment, and its companion term, pulse, from earlier accounts. The model is based on hiearchical, statistical prediction, modeling expectations of both what an event will be and when it will happen. As such,it constitutes a kind of predictive coding, with a particular novel hypothetical implementation. Here, we focus on the model’s mechanism for predicting when a perceptual event will happen, given an existing sequence of past events, which maybe musical or linguistic. We propose a range of tests to validate or falsify the model, at various different levels of abstraction, and argue that computational modelling in particular, and this model in particular, can offer a means of providing limited but useful evidence for evolutionary hypotheses.